VD_FINDINFO HC / 2019 / 466 vom 7. Juni 2019 - VD Tribunal cantonal (2019)
CONSTATATION DES FAITS, IMMEUBLE AGRICOLE, UNITÉ DE MAIN-D'OEUVRE STANDARD, EXPLOITATION AGRICOLE, ATTRIBUTIONSENS GÉNÉRAL | 36 LDFR, 310 CPC (CH), 318 al. 1 let. c ch. 2 CPC (CH)